Malondialdehyde-Deoxyguanosine Adduct Formation in Workers of Pathology Wards. The Role of Air Formaldehyde Exposure - Bono, Roberto (2010)
BACKGROUND: Formaldehyde is a ubiquitous pollutant to which humans are exposed. Pathologists can experience high formaldehyde exposure levels. Formaldehyde – among other properties – induce oxidative stress and free radicals, which react with DNA and lipids, leading to oxidative damage and lipid peroxidation, respectively. We measured the levels of air-formaldehyde exposure in a group of Italian pathologists and controls. We analyzed the effect of formaldehyde exposure on leukocyte malondialdehyde-deoxyguanosine adducts (M(1)-dG), a biomarker of oxidative stress and lipid peroxidation. We studied the relationship between air-formaldehyde and M(1)-dG adducts. METHODS: Air-formaldehyde levels were measured by personal air samplers. M(1)-dG adducts were analyzed by (32)P-postlabelling assay. RESULTS: Reduction rooms pathologists were significantly exposed to air-formaldehyde in respect to controls and to the pathologists working in other laboratory areas (p<0.001). A significant difference for M(1)-dG adducts between exposed pathologists and controls was found (p=0.045). The effect becomes stronger when the evaluation of air-formaldehyde exposure was based on personal samplers (p=0.018). Increased M(1)dG adduct levels were only found in individuals exposed to air-formaldehyde concentrations higher than 66 μg/m(3). When the exposed workers and controls were subgrouped according to smoking, M(1)-dG tended to increase in all the subjects but a significant association between M(1)-dG and air-formaldehyde was only found in not smokers (p= 0.009). Air formaldehyde played a role positive but not significant (r = 0.355, p = 0.075, Pearson correlation) in the formation of M(1)-dG, only in not smokers. CONCLUSIONS: Working in the reduction rooms and to be exposed to air-formaldehyde concentrations higher than 66 μg/m(3) is associated with increased levels of M(1)-dG adducts.